2011
DOI: 10.1128/jb.05620-11
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bifidobacterium longum subsp. longum KACC 91563

Abstract: Bifidobacterium longum strains predominate in the colonic microbiota of breast-fed infants. Here we report the complete genome sequence of B. longum subsp. longum KACC 91563, isolated from feces of neonates. A single circular chromosome of 2,385,301 bp contains 1,980 protein-coding genes, 56 tRNA genes, and 3 rRNA operons.Members of the genus Bifidobacterium are prevalent in the human colon and represent up to 90% of all bacteria in fecal samples of breast-fed infants and 3 to 5% of adult fecal microbiota (7,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…19,26,27 According to TEM analysis, B longum KACC 91563 and E faecalis KACC 91532 are rod-shaped and roundshaped bacteria, respectively (see Fig E1, A, in this article's Online Repository at www.jacionline.org). Because it was uncertain whether these 2 kinds of microbiota would reach the intestines of mice intact, we orally administered E faecalis KACC 91532 and B longum KACC 91563 for 2 weeks and observed bacteria in fecal samples using FISH.…”
Section: B Longum Kacc 91563 Attenuates Food Allergy Symptoms In a Momentioning
confidence: 99%
“…19,26,27 According to TEM analysis, B longum KACC 91563 and E faecalis KACC 91532 are rod-shaped and roundshaped bacteria, respectively (see Fig E1, A, in this article's Online Repository at www.jacionline.org). Because it was uncertain whether these 2 kinds of microbiota would reach the intestines of mice intact, we orally administered E faecalis KACC 91532 and B longum KACC 91563 for 2 weeks and observed bacteria in fecal samples using FISH.…”
Section: B Longum Kacc 91563 Attenuates Food Allergy Symptoms In a Momentioning
confidence: 99%
“…Bifidobacteria are Gram-positive bacteria which are commonly present in healthy human’s intestinal tract; especially they occupy approximately 90% of total bacteria in feces of breast-fed infants and about 3% to 5% in adult fecal microbiota (Ham et al, 2011). Through the application of genomic sequencing technique, it has been shown that Bifidobacterium longum is absent from virulence and pathogenicity factors and it is considered as the safest bacteria without health hazards (Meile et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These products are the respective metabolites biotransformed by intestinal microflora, when loganin, arctiin and ginsenoside Rb1 were orally administered. 1,26) The metabolites arctigenin and ginsenoside Rd exhibit more potent biological effects in vitro than their parental compounds. 37,38) However, the biological activities of loganetin, a metabolite of loganin, have not been studied.…”
Section: +mentioning
confidence: 99%
“…longum KACC91563 (GenBank protein accession number CP002794). 26) Expression and Purification of the rBglX In order to investigate the enzymatic property of the rBglX in E. coli, the rBglX was expressed by inserting the cloned gene along with the codon of its signal peptide into the KpnI and HindIII sites of pET-39b(+) vector, which has N-terminal and C-terminal 6×His tag. The pET 39b(+) vector has DsbA, which is the periplasmic enzyme that catalyzes the formation and isomerization of disulfide bond and is used for the purpose of enhancing solubility.…”
Section: Cloning and Sequencing Of Bglx From B Longum H-1mentioning
confidence: 99%